Contending Images of World Politics: Penelusuran Kritis terhadap Asal-Usul dan Perdebatan Mengenai Konsep ‘Developing Countries’ - Dafri Agussalim (Jurnal Hubungan Internasional, 2019)
This article is a critical tracer study of genealogy and development, including debates on the concepts and terminology of developing countries. By applying constructivism perspective, it aims to explain the meaning, categories, and criteria, the emergence and development of the idea, and the reason why these concepts and ideas have been changing from time to time. This article argues that the ontological existence (concepts and ideas) of the developing countries is the result of construction of agents both foreign countries–especially the western–and developing countries themselves. Therefore, the conceptualization of developing countries is inseparable from values and (self-)interest of each country, whether it is political, ideological, or economical. As a result, there must be possibilities of inconsistency from the agent in making categorization. This inconsistency is influenced by the changing of identity, world view, interests, and policies of the agents as an impact of geopolitical and geostrategic change in the world after Cold War. The significant economic and political development which has been experienced by some developing countries and the increasing of economic and political problems faced by some developed countries has forced the agents to reconceptualized their identity, interest, and foreign policy toward what so called developing countries.